Sum of Products of Subsets

Consider the set S = { 1 , 2 , 4 , . . . , 2 100 } S=\left\{1, 2, 4, ..., 2^{100}\right\} . There are 2 101 1 2^{101}-1 non-empty subsets of this set.

For each subset A A let f ( A ) f(A) be the product of the elements in that subset. For example, if A = { 1 , 2 , 4 } A=\{1, 2, 4\} then f ( A ) = 8 f(A)=8 .

Find the sum of all f ( A ) f(A) as A A ranges over all the 2 101 1 2^{101}-1 subsets. If the answer when divided by 126 126 leaves a remainder of x x then find x x .


The answer is 89.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

John Mistele
Sep 22, 2014

We can re-interpret the sum of the f(A) for all A as

n = 0 100 ( 2 n ) ( g ( n ) ) \sum_{n = 0}^{100} (2^n)(g(n))

Where g(n) = "the number of ways to partition n into the sum of any number of distinct non-negative integers less than or equal to 100"

It is important to say "non-negative" because we know f ( A ) = ( 2 a 1 ) ( 2 a 2 ) . . . ( 2 a k ) f(A) = (2^{a_1}) ( 2^{a_2} )...(2^{a_k})

for some k positive integers a_i, and since 1 = 2^0 may be an element of A, one of the a's may be zero.

Daunting as this "g" function and its poorly worded definition may seem, it can be recognized as the coefficient of x^n in the expression ( x 0 + 1 ) ( x 1 + 1 ) . . . ( x 100 + 1 ) 1 (x^0+1)(x^1+1)...(x^{100} + 1) - 1

(The "-1" corrects for the case of an empty set A.)

Thus our answer will be y, as defined below:

( 2 0 + 1 ) ( 2 1 + 1 ) . . . ( 2 100 + 1 ) 1 = y ( m o d 126 ) (2^0+1)(2^1+1)...(2^{100} + 1) - 1 = y (mod 126)

Since 126 = 9x2x7, and 2 and 9 are factors of y+1, we must simply evaluate y + 1 mod 7. Since the order of 2 mod 7 is 3, our (2^n + 1) terms are all either 2, 3, or 5 mod 7, and thus we have y + 1 = [ ( 2 ) ( 3 ) ( 5 ) ] 33 ( 2 ) ( 3 ) = 2 33 = 1 ( m o d 7 ) y+1 = [(2)(3)(5)]^{33}(2)(3) = -2^{33} = -1 (mod 7)

we have that y +1 is a multiple of 18 congruent to 6 mod 7, and is thus 90.

So, finally, y = 89 y= \boxed{89}

Rindell Mabunga
Sep 20, 2014

Let e k e_k be the k k th degree elementary symmetric polynomial

Then the sum of all f ( A ) = e 1 + e 2 + e 3 + . . . + e 100 f(A) = e_1 + e_2 + e_3 + ... + e_{100}

f ( A ) = e 1 + e 2 + e 3 + . . . + e 100 f(A) = e_1 + e_2 + e_3 + ... + e_{100}

f ( A ) = ( e 1 + 1 ) ( e 2 + 1 ) ( e 3 + 1 ) . . . ( e 100 + 1 ) 1 f(A) = (e_1 + 1)(e_2 + 1)(e_3 + 1)...(e_{100} + 1) - 1

Using modulo 126 126 ,

f ( A ) ( m o d 126 ) = 2 ( 3 ) ( 5 ) ( 17 ) ( 33 ) ( 65 ) ( 3 ) ( 5 ) . . . ( 3 ) ( 5 ) ( 17 ) ( 33 ) 1 f(A)(mod 126) = 2(3)(5)(17)(33)(65)(3)(5)...(3)(5)(17)(33) - 1

When simplified,

f ( A ) ( m o d 126 ) = 89 ( m o d 126 ) f(A)(mod 126) = \boxed{89}(mod 126)

Sorry, i need to hurry. At least, i gave you an idea/outline on solving this problem.

the sum would be -

( 2 0 + 1 ) ( 2 1 + 1 ) ( 2 2 + 1 ) . . . ( 2 100 + 1 ) (2^{0} + 1)(2^{1} + 1)(2^{2} + 1) . . . (2^{100} + 1)

which gives a remainder 18 18 . please tell where I went wrong.

Rohit Kumar - 6 years, 8 months ago

Log in to reply

The correct recurrence is a n + 1 = ( 2 n + 1 + 1 ) a n + 2 n + 1 a_{n+1} = (2^{n+1} + 1)a_n + 2^{n+1} . I think you might be missing the + 2 n + 1 + 2^{n+1} term, which comes from the one-element set { 2 n + 1 } \{ 2^{n+1} \} .

Patrick Corn - 6 years, 8 months ago

Log in to reply

finally found out my error. thanks !

Rohit Kumar - 6 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...